PWE-015 Pudendal Nerve Stimulation for Faecal Incontinence. (4th June 2013) - Thomas, G; George, A; Dudding, T; Nicholls, R J; Vaizey, C
Abstract : Introduction: Sacral nerve stimulation (SNS) is an established treatment for faecal incontinence (FI). However, only 50–60% of patients will have a good response to SNS. Further treatment is difficult for those who do not respond to SNS. Pudendal nerve stimulation (PNS) was first reported for FI in 2005. Since then only one small study has further reported its use for FI. We aimed to assess PNS for FI in those who have failed to improve with SNS. Methods: Recruited patients underwent test PNS. Those who experienced a ≥ 50% reduction in frequency of FI episodes underwent permanent PNS. The primary outcome measure was the change in frequency of FI episodes. Further outcome measures were further bowel diary data, St Marks FI Score, Rockwood FI QOL Score, SF-36 QOL Score and anorectal physiological changes. Results: Ten patients underwent test PNS. Five experienced a ≥ 50% improvement in frequency of FI episodes, and underwent permanent stimulation. One withdrew from the study at six months. At median follow up of 24 (3–36) months, the median frequency of FI improved from 5 (18.25) to 2.5 (3) per week; p = 0.043. Three maintained a ≥ 50% improvement in soiling. There was a significant improvement in the St Marks FI score, 19 (6) to 16 (4.5); p = 0.042. There were no significant changes in the ability to defer defecation or in quality of life measures. Conclusion: PNS may be an effective treatment for FI for those who have failed to improve with SNS Disclosure of Interest: None Declared.